2003
DOI: 10.1256/qj.02.186
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of model‐simulated trends in stratospheric temperatures

Abstract: SUMMARYEstimates of annual-mean stratospheric temperature trends over the past twenty years, from a wide variety of models, are compared both with each other and with the observed cooling seen in trend analyses using radiosonde and satellite observations. The modelled temperature trends are driven by changes in ozone (either imposed from observations or calculated by the model), carbon dioxide and other relatively well-mixed greenhouse gases, and stratospheric water vapour.The comparison shows that whilst mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

36
245
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(285 citation statements)
references
References 37 publications
(24 reference statements)
36
245
0
Order By: Relevance
“…These results are broadly in agreement with previous estimates of the relative contribution of ozone depletion and CO 2 cooling to the upper stratospheric temperature trends (Shine et al, 2003;Jonsson et al, 2009). The exact contribution assigned to ODSs will be sensitive to the magnitude of ozone depletion in the model, though the decrease of ozone in these CMAM REF-B2 experiments is roughly in agreement with observations in the mid to upper stratosphere (Jonsson et al, 2009).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…These results are broadly in agreement with previous estimates of the relative contribution of ozone depletion and CO 2 cooling to the upper stratospheric temperature trends (Shine et al, 2003;Jonsson et al, 2009). The exact contribution assigned to ODSs will be sensitive to the magnitude of ozone depletion in the model, though the decrease of ozone in these CMAM REF-B2 experiments is roughly in agreement with observations in the mid to upper stratosphere (Jonsson et al, 2009).…”
Section: Resultssupporting
confidence: 92%
“…Cooling in the upper stratosphere is largely a result of decreases in ozone, decreasing the shortwave heating by ozone, and increases in longwave cooling from increasing CO 2 (Shine et al, 2003). Comparing temperature trends of the REF-B2 and GHG simulations, we find that for the 1979-2000 period CO 2 , with a small additional contribution from increasing H 2 O, contributes a minimum of 60% of the total cooling found in REF-B2 at the stratopause, with larger contributions above and below.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is reflected in the expanding region of reduced RH from the midtroposphere to the surface in the poleward flank of the climatological dry zones (regions with RH < 40), where the RH deficit is at a maximum. The increased RH near the tropopause and lower stratosphere is associated with the cooling from increased longwave radiative loss to space under global warming (35,36). Even a small increase in moisture due to enhanced vertical transport will result in a large increase in RH in these regions.…”
Section: Meridional Outflow and Relative Humiditymentioning
confidence: 99%
“…the uptake and subsequent sedimentation of HNO 3 within Polar Stratospheric Clouds, PSC's) both increases and prolongs stratospheric ozone loss (Crutzen and Arnold, 1986;Fahey et al, 1989;Fahey et al, 1990). Although this process is more prevalent and intense in the Antarctic winter stratosphere, as a consequence of lower temperatures, Shine et al (2003) have conducted a recent comparison of stratospheric temperature changes and found that one possible outcome is that a future cooling could occur in the Arctic which would result in an increase in the importance of denitrification in the Arctic winter stratosphere. Moreover,during the last decade, observational evidence of this vertical redistribution of HNO 3 in the Arctic stratosphere has also been found (e.g.…”
Section: Introductionmentioning
confidence: 99%